2010
DOI: 10.2174/1877610801002010001
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Mechanism of Nickel and Zinc-Nickel Alloy Electrodeposition

Abstract: The mechanism of electrochemical deposition of nickel and zinc-nickel alloy was described as in actually science literature. To prove practically the proposed mechanism, it was used as interesting effect which consists in an increase of the deposited mass more than Faraday law predicts. Nickel was deposited and zinc-nickel alloy was codeposited using a potentiostat-galvanostat Parstat 2273 coupled with an Electrochemical Quartz Crystal Microbalance (EQCM). The mass distribution of deposited metal and alloy was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…The mechanism of Zn–Ni alloy deposition on to MS substrate, the chemical reactions that occur on the cathode (MS) follow two steps, as described in [11,12]. Zinc ions and Nickel ions are deposited on the MS substrate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of Zn–Ni alloy deposition on to MS substrate, the chemical reactions that occur on the cathode (MS) follow two steps, as described in [11,12]. Zinc ions and Nickel ions are deposited on the MS substrate.…”
Section: Resultsmentioning
confidence: 99%
“…This may be explained by 'hydroxide suppression mechanism', where zinc hydroxy compounds inhibit the nickel deposition [7][8][9][10]. Vasilache et al described the mechanism of electrochemical deposition of nickel and zinc-nickel alloy [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…26,[28][29][30][31][32][33][34][35] In Fig. 5d, the experimental curve of current density versus time in an oxygen reduction reaction, which was reported by Bergel et al 17 among several supporting data, 17,[36][37][38][39][40] is compared with the theoretical calculations to illustrate the electrochemical theory. The two particle number constants of activation and concentration polarization are required to validate the theoretical values.…”
Section: Comparison Results Of Polarizationmentioning
confidence: 99%
“…Recently, in a comparative study between five additives [22], the PVP is found to be the best additive which decreased grain size of the copper powder to a minimum threshold. To the best of our knowledge, a very few studies have been dedicated to the study of PVP effect on nickel electrodeposition [24]. Furthermore, and unlike SDS, no report has been published on the effect of PVP on the brightness of nickel electrodeposition.…”
Section: Introductionmentioning
confidence: 99%